2021
DOI: 10.26525/jtfs2021.33.3.290
|View full text |Cite
|
Sign up to set email alerts
|

Physical and Mechanical Properties of Glued Laminated Bamboo Lumber

Abstract: Glued laminated bamboo lumber (GLBL) made of Dendrocalamus asper, Dendrocalamus giganteus, Dendrocalamus latiflorus and Gigantochloa levis has potential to overcome the shortage of wood supply. The objective of the study was to determine the effects of bamboo species on the properties of GLBL. Laboratory-scale GLBL was manufactured from 26−28 bamboo strips from each bamboo species, assembled vertically, glued with 250 g m -2 of water-based polymer-isocyanate, and applied force horizontally on the wooden clamps… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 4 publications
0
6
1
Order By: Relevance
“…In this way, it is necessary to split bamboo into small elements that can be used to produce material with varying sizes and cross-sections (Ni et al 2016). Several studies related to bamboo products have been conducted by several authors, such as the analysis of glued laminated bamboo beams under bending (de Lima et al 2014), laminated bamboo lumber production Ando 2000, 2001), bamboo oriented boards (Sumardi et al 2007), glued laminated bamboo (Nugroho and Ando 2000;Correal and Lopez 2008;Paes et al 2009;Rusch et al 2019;Sulastiningsih et al 2021), heat-treated glued laminated bamboo (Brito et al 2018), bamboo-reinforced composites (Corradi et al 2009), adhesive performance and structural behavior , laminated bamboo lumber (Mahdavi et al 2012;Kitiyanun et al 2022), parallel strand bamboo (Huang et al 2013), bamboo-bundle laminated veneer lumber (Chen et al 2014), structural performance, and laminated bamboo panels (Rusch et al 2019). In addition, research has been carried out related to the manner in which trusses are prepared from glued laminated bamboo ( de Lima et al 2015).…”
Section: Introductionmentioning
confidence: 99%
“…In this way, it is necessary to split bamboo into small elements that can be used to produce material with varying sizes and cross-sections (Ni et al 2016). Several studies related to bamboo products have been conducted by several authors, such as the analysis of glued laminated bamboo beams under bending (de Lima et al 2014), laminated bamboo lumber production Ando 2000, 2001), bamboo oriented boards (Sumardi et al 2007), glued laminated bamboo (Nugroho and Ando 2000;Correal and Lopez 2008;Paes et al 2009;Rusch et al 2019;Sulastiningsih et al 2021), heat-treated glued laminated bamboo (Brito et al 2018), bamboo-reinforced composites (Corradi et al 2009), adhesive performance and structural behavior , laminated bamboo lumber (Mahdavi et al 2012;Kitiyanun et al 2022), parallel strand bamboo (Huang et al 2013), bamboo-bundle laminated veneer lumber (Chen et al 2014), structural performance, and laminated bamboo panels (Rusch et al 2019). In addition, research has been carried out related to the manner in which trusses are prepared from glued laminated bamboo ( de Lima et al 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Similar results were obtained in the bending resistance values of the specimens produced in previous studies on parallel-strand lumber produced with different adhesives. It has been reported that this increase, depending on the type of adhesive, may be due to the type of adhesive and the carbon-carbon bonds formed during polymerization (Marra 1992;Wu et al 1998;Simpson et al 1999;Sulastiningsih et al 2005;Ahmad and Kamke 2011;Li et al 2015;Gong et al 2016;He et al 2018;Sulastiningsih et al 2021;Qiu et al 2022).…”
Section: Resultsmentioning
confidence: 99%
“…Bamboo, commonly known as “the second forest”, is abundant in Southwest China. , As a sustainable, readily available, and biodegradable material with a short maturity rotation (4–5 years), bamboo is widely employed as a notable nontimber building material for flooring and furniture manufacturing (e.g., bamboo particle board (BPB), bamboo mat board, laminated bamboo board, bamboo scrimber, and bamboo mat veneer composite). One of the key challenges in a bamboo-based board is the release of a carcinogenic substance from formaldehyde-based adhesives widely used in the wood industry. Nonformaldehyde-based adhesives, such as cornstarch, soy protein, , magnesium oxychloride, and aluminophosphate, have attracted extensive attention owing to them being formaldehyde-free, nontoxic, having rich sources, and so forth. However, the use of such adhesives is also limited by the poor fungal resistance, complicated fabrication process, and weak wet bonding strength …”
Section: Introductionmentioning
confidence: 99%